ANALYSIS OF PROVIDING INCOME IMPROVEMENT BENEFITS (TPP) IN INCREASING THE PERFORMANCE OF STATE CIVIL APPARATUS (ASN) IN BARRU DISTRICT SOCIAL SERVICES OFFICE - Pratiwi, Dian; Masyitah (Meraja journal, 2023)
Copyright (c) 2023 Meraja journal